Analysis Of Nurses Competency To Preparedness In Facing Disasters In Regional Public Hospitals Of Ende District, East Nusa Tenggara Province 2020 - Irwan Budiana; Yustina Pacifica Maria Paschalia; Yoseph Woge; Agus Supinganto (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Disasters are a series of events that threaten and disrupt people's lives and livelihoods which can be caused by natural and non-natural factors. One of the ways to handle disasters in hospitals is by nurses who have standardized competence. This study aims to determine the relationship between nurse competence and disaster preparedness. This study uses a quantitative design method with a correlational analytic approach. Processing data using the Spearman Rank correlation test with the help of the SPSS program for Windows 16.00. Results of reseacrh is Knowledge has a significant relationship with disaster preparedness with a value of 0.001 (p-value <0.05) and attitude variables also have a significant relationship with disaster preparedness with a value of 0.007 (p-value <0.05). ) and the skill variable also has a significant relationship to disaster preparedness with a value of 0.043 (p-value <0.05). Nurse competence has a relationship with disaster preparedness in the hospital.